Psychosocial work characteristics and sleep quality: a systematic review of longitudinal and intervention research - Michelle Van Laethem; Debby GJ Beckers; Michiel AJ Kompier; Ap Dijksterhuis; Sabine AE Geurts (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVES: The objective of this study was to review longitudinal and intervention studies examining the association between psychosocial work characteristics (eg, job demands, job control, and social support) and sleep quality. Our main research aims were to examine whether (i) psychosocial work characteristics are a predictor of sleep quality, and (ii) sleep quality, in turn, is a predictor of psychosocial work characteristics. METHODS: A systematic literature search resulted in 20 relevant papers, of which 16 were longitudinal studies and 3 were intervention studies (1 study was discussed in separate papers). To quantify results, we assessed the strength of evidence of all examined associations and subsequently evaluated the studies' research quality based on predefined quality criteria. RESULTS: One intervention and three longitudinal studies studies were categorized as being of high-quality. In longitudinal studies, we found consistent and strong evidence for a negative relation between job demands and sleep quality as well as evidence for a positive relation between job control and sleep quality. Other psychosocial work characteristics were examined in an insufficient number of (high-quality) studies. Moreover, both intervention studies as well as studies investigating reversed and reciprocal relations are rare, which further limits the possibility of drawing conclusions on causality. CONCLUSIONS: Based on the current literature, it can be concluded that high job demands and low job control are predictors of poor sleep quality. More high-quality research is needed to examine the possible causal relationship between these and other psychosocial work characteristics with sleep quality, in addition to research focusing on reversed and reciprocal relations.